Hubungan Supervisi Kepala Sekolah Dan Konsep Diri Dengan Kedisiplinan Kerja - Apan Apan (Jurnal Bisnis dan Ekonomi, 2026)
Teachers’ work discipline is influenced by various interrelated factors. In addition to the professional competencies that every teacher must possess, there are other factors that play a role in shaping their level of discipline, including supervision by the principal and teachers’ self-concept. These two factors are believed to contribute to teachers’ success in carrying out their duties and responsibilities professionally. Objective : This study aims to analyze the relationship between principal supervision and teachers’ self-concept on teachers’ work discipline. Methods : This study employed a quantitative approach, involving all 54 teachers as the study population. Data were collected by distributing questionnaires to all respondents. The data were then analyzed using descriptive statistics, correlation analysis, regression analysis, and hypothesis testing via t-tests and F-tests using SPSS version 20.   Research Results : The results of the study indicate that there is a positive, strong, and significant relationship between principal supervision and teacher work discipline. The principal supervision variable accounts for 28.4% of the variance in teacher work discipline, while the remaining 71.6% is influenced by other factors not included in this study. In addition, the study also found a strong and significant positive relationship between teachers’ self-concept and their work discipline. Self-concept accounts for 25.4% of the variance, while the remaining 74.6% is explained by other variables outside the scope of this study. Furthermore, when principal supervision and teachers’ self-concept were analyzed simultaneously, both variables showed a positive, strong, and significant relationship with teachers’ work discipline. Together, they accounted for 30.2% of the variance in teachers’ work discipline, while the remaining 69.8% was influenced by other factors not examined in this study. These findings suggest that improving the quality of supervision provided by the principal, coupled with the development of a positive self-concept among teachers, can serve as a key strategy for enhancing work discipline, thereby enabling teachers to perform their professional duties more effectively.